HUBUNGAN MINUMAN KARIOGENIK TERHADAP PREVALENSI KARIES GIGI ANAK USIA SEKOLAH DASAR - Assyifa Fadilah Dwiputri; Yenni Hendriani Praptiwi; Tiurmina Sirait; Isa Insanuddin (Poltekkes Kemenkes Bandung, 2022)
Dental and oral health is important for the health in general. One of the dental diseases is dental caries, dental caries is a serious health problem for school-age children because in general children like sweet drinks such as ice, milk, sweet drinks and the like. Many types of fast food drinks are sold in various places, thereby increasing children's interest in consuming these foods and beverages. Consuming cariogenic drinks with high frequency can increase the risk of caries. This study aims to determine the relationship of cariogenic drinks to the prevalence of dental caries in elementary school age children at SDN 036 Ujungberung, Bandung. This research is a quantitative analytical research with a cross-sectional. This research was conducted by conducting direct examination of children and filling out questionnaires. Sampling technique was carried out using the purposive sampling with a sample of 78 respondents. Data processing was carried out quantitatively by collecting data on the frequency of cariogenic drink consumption and caries prevalence data. The results of this study showed that the prevalence of caries was 59.0%, the frequency of consumption of cariogenic drinks was the highest percentage obtained by students with high levels of cariogenic drink consumption, namely 41.0% which stated that there was no relationship between cariogenic drink consumption and the prevalence of dental caries in elementary school-aged children at SDN 036 Ujungberung. Bandung.